Prospective Chemistry and Science Teachers' Views and Metaphors about Chemistry and Chemical Studies - ÖNEN ÖZTÜRK, FATMA; AĞLARCI ÖZDEMİR, OYA (ANI YAYINCILIK, 2017)
Purpose: The aim of this study was to examine the metaphors created by prospective chemistry and science teachers and their views about how the studies in the field of chemistry are carried out in relation to the grade level and department. Research Methods: Case study as a qualitative research design was used. Participants in the study included 16 freshmen and 25 senior prospective chemistry teachers and 52 freshmen and 41 senior prospective science teachers. The data were analyzed with content analysis. Findings: The findings revealed that prospective teachers' views of chemistry were generally correct. However, a few of the participants' views were embedded with misconceptions. Also, the metaphors showed that they had different views toward chemistry. Implications for Research and Practice: The views of prospective chemistry and science teachers are similar to each other, and the results are more comprehensive and detailed for the last-grade students. When prospective teachers' metaphors about the chemistry and justifications are compared in terms of grade levels, it is seen that the justifications put forth have various similarities and differences. When the findings obtained from the research are compared in terms of different fields, similarities and differences are present together in the results. It is seen that the metaphors set up by the prospective teachers are quite different from one another when they are compared in terms of the fields. It can be suggested that metaphors in different concepts and topics could be examined and studies could be conducted by determining the gaps in those areas. (C) Ani Publishing Ltd. All rights reserved.
Keywords: Teacher education; science education; chemistry education; teacher candidate; student perspectives; CONCEPTIONS